PENINGKATAN KINERJA SUMBER DAYA MANUSIA BERBASIS ROLE STRESSOR DENGAN MODERASI MODAL SOSIAL - Muhazir Muhazir (Jurnal Riset Bisnis Indonesia, 2013)
This study sampled all the treasurers and the board items within Health Officeof ButonUtara District.This research aims to investigate: (1) the influence of role conflict on role ambiguity of treasurers,managers, and storages of goods, (2) the influence of role conflict and role ambiguity on theperformance of treasurers, managers, and storages of goods, and (3) the influence of social capitalas moderating on role of conflict and role of ambiguity on the performance of treasurers, managers,and storages of goods. Data were analyzed by Visual Partial Least Square (VPLS) technique. Theresults showed that the role conflict affected the performance of the employees with negative effects.Moreover, the role conflict also affected the role ambiguity but the role ambiguity did not affect theperformance of the employees. Moderating variable of social capital can weaken the influence of therole conflict on the performance of the employees. However, social capital was not a moderation ofthe relationship between role ambiguity and the performances of the employees.Keywords: Role Ambiguity, Role Conflict, Performance, Social Capital